Implementation Of Hydroponic Device Control System Via Website - Hamdani; Benny Satria; Irfan Fatahanan (Journal of Information Technology, computer science and Electrical Engineering, 2024)
Hydroponics is a method of farming without using soil, usually carried out in a glass room using water as a medium containing nutrient. The hydroponic farming method is considered suitable for use in densely populated areas with limited agricultural land. The flow of water that carries nutrients for plants must be regulated as well as possible to support optimal plant growth. The focus of this research is to design a water flow control system that carries nutrients automatically and can be monitored and controlled remotely using the internet. Water conditions are read by sensors and processed by the ESP8266 microcontroller. Monitoring results are displayed via LCD and via website. Control of the nutrient-carrying water pump is also done via the website. With this system, hydroponic farmers can monitor and control the water and nutrient flow system remotely.